The physiological effects of beverage ingestion during cross country ski training in elite collegiate skiers - Seifert, J. G.; Luetkemeier, M. J.; White, A. T.; Mino, L. M. (Canadian Journal of Applied Physiology, 1998)
The purpose of this study was to investigate the effects of beverage ingestion on fluid balance during 1.5 hr of low intensity cross country skiing. In Part I, 6 skiers drank water ad libitum during ski training. In Part II, 10 skiers were matched by body weight (BW) and assigned to ingest 2.5 ml.kg-1 BW of water or a carbohydrate/electrolyte (CE) beverage every 2.5 km. Skiing speed averaged 11.5 km.hr-1 for 90 min around a 5 km groomed track. Following 20 min of seated rest, blood samples were collected immediately before and approximately 30 min after skiing. Part I data indicated that subjects ingested 576 +/- 189 ml of fluid and produced 266 +/- 205 ml of urine; BW, plasma and urine osmolality, and plasma protein decreased significantly. In Part II, the CE group produced less urine (135u75 vs. 450 +/- 262 ml) and had smaller decreases in plasma osmolality (-1.0 +/- 1.0 vs. -7.0 +/- 2.4 mOsm.kg H2O) and protein (-0.11 +/- 08 vs. -0.42 +/- 0.24 gL-1) than the water group. No differences were observed for BW loss, % change in PV, FWC, or change in urine osmolality. It was concluded that ad lib water ingestion was inadequate to minimize fluid balance disruption. Plain water ingestion also led to significant dilution of the plasma and increased urine output. However, the ingestion of CE led to attenuation of fluid balance disruption, presumably due to the maintenance of osmotic balance in the plasma.